Neurotropin Inhibits Lipid Accumulation by Maintaining Mitochondrial Function in Hepatocytes via AMPK Activation - Wang, Qinglan; Wang, Zhijun; Xu, Mingyi; Tu, Wei; Hsin, I-Fang; Stotland, Aleksandr; Kim, Jeong Han; Liu, Ping; Naiki, Mitsuru; Gottlieb, Roberta A.; Seki, Ekihiro (Frontiers in Physiology, 2020)
The appearance of lipid droplets in the cytoplasm of hepatocytes, known as hepatic steatosis, is a hallmark of nonalcoholic fatty liver disease. Inhibiting hepatic steatosis is suggested to be a therapeutic strategy for NAFLD. The present study investigated the actions of Neurotropin, a drug used for chronic pain in Japan and China, on lipid accumulation in hepatocytes as a possible treatment for NAFLD. NTP inhibited lipid accumulation induced by palmitate and linoleate, the two major hepatotoxic free fatty acids found in NAFLD livers. An RNA sequencing analysis revealed that NTP altered the expression of mitochondrial genes. NTP ameliorated palmitate- and linoleate-induced mitochondrial dysfunction by reversing mitochondrial membrane potential, respiration, and beta-oxidation, suppressing mitochondrial oxidative stress, and enhancing mitochondrial turnover. Moreover, NTP increased the phosphorylation of AMPK, a key factor in the regulation of mitochondrial function, and induced PGC1b expression. Inhibition of AMPK activity and PGC1b expression diminished the anti-steatotic effect of NTP in hepatocytes. JNK inhibition could also be associated with NTP mediated inhibition of lipid accumulation, but we did not find the association between AMPK and JNK. These results suggest that NTP inhibits lipid accumulation by maintaining mitochondrial function in hepatocytes via AMPK activation, or by inhibiting JNK.